You can substitute what y is into the second equation, so:
3x + 4(2x + 1) = 26
3x + 8x + 4 = 26
11x + 4 = 26
- 4
11x = 22
÷ 11
x = 2
y = (2 × 2) + 1
y = 5 + 1
y = 5
So you get x as 2 and y as 5, I hope this helps!
Answer:
-5/3
Step-by-step explanation:
Do PEMDAS
8 - 11 = -3
-3 ^ 3 = -27
-(-27) = 27
I-14I = 14
3 x 14 = 42
27 - 42 = -15
2^4 = 16
16 - 7 = 9
-15/9 = -5/3
Answer:
(0;-4)
(-6;4)
Step-by-step explanation:
-8x - 6y - 7 = 17
-8x-6y-24=0
y=-(4x)/3-4
(3;0)
-(4*3)/3-4=8
8≠0
(-2;-1)
-(4*(-2))/3-4=-4/3
-4/3≠-1
(0;-4)
-(4*0)/3-4=-4
-4=-4
(-9;6)
-(4*(-9))/3-4=8
8≠6
(-6;4)
-(4*(-6))/3-4=4
4=4
The standard form of a line is in the form
![Ax + By = C](https://tex.z-dn.net/?f=Ax%20%2B%20By%20%3D%20C)
A, B and C are integers, and A is positive. Let's start with multiplying the whole equation by 3 to get rid of denominators:
![3y+6=x](https://tex.z-dn.net/?f=3y%2B6%3Dx)
Subtract 3y from both sides:
![6=x-3y](https://tex.z-dn.net/?f=6%3Dx-3y)
Which of course is equivalent to
![x-3y=6](https://tex.z-dn.net/?f=x-3y%3D6)
Which is the standard form, given the coefficients A=1, B=-3, C=6.